Corporate Personhood, Again? - Gerencser, Steven (Journal of Leadership, Accountability and Ethics, 2023)
The idea of the corporate person continues to present problems for politics, especially through the framing of corporate power and responsibilities as legal questions. Meanwhile, traditional theories of liberalism and pluralism struggle to comprehend the corporation as either a participant in politics or a site where politics occur. Theorists of democracy likewise express anxiety about the impact of corporations even while theorists of business ethics invoke the notion of corporate citizenship to restrain corporations through democratic ethics. This article analyzes recent contributions to debates about the role of corporations as legal persons. The article then argues that legal debates, while important, can also serve to limit an understanding of the social and political contexts in which economic actors like corporations exercise power. Recognizing those limits reveals the need for a broader range theoretical frameworks beyond the legal to comprehend corporate power.